The role of simultaneous stereotactic biopsy and radiofrequency ablation in the management of brain neoplasms in countries with limited financial resources - Mohamed Ashraf Mahmoud; Abdelrahman El Gayar; Shafik T El Molla; Hesham Radwan; Tarek H El Serry; Ashraf Al Abyad (Egyptian Journal of Neurosurgery)
Abstract Background Heat can help control the progression of intra-axial cerebral neoplasms in selected cases. RF (Radiofrequency) is available and cost effective in resource-limited settings. RF stereotactic heat was delivered simultaneously with the biopsy in brain tumors. Objective We evaluated the safety and feasibility of stereotactic RF ablation of intra-axial brain neoplasms during stereotactic brain biopsy procedure. Methods Twenty-two adult patients were treated with interstitial hyperthermia by RF plus stereotactic brain tumor biopsy in Ain shams University Hospitals from 2022 to 2024. Follow-up for tumor progression was done over a period of 12 months. Results A total of 22 participants have been enrolled; follow-up period was 12 months. There were 12 (54.5%) females and 10 (45.5%) males. The mean and median ages were 53.6 years (range 25–72) and 54 years, respectively. 72.6% had at least a single baseline comorbidity. From the ablated tumors, 17 were primary, 4 were metastatic, and 1 was in-field necrosis. Median tumor volume was 6 cm3 and mean was 10.2 cm3 (range, 0.5–40 cm3). The one-year estimated survival rate was 86.6%, and this was impacted by disease etiology. Conclusions Results from this study demonstrate that RF ablation is a safe technique that it can be used simultaneously with stereotactic biopsy in selected cases of intra-axial brain neoplasms. A potential trend of longer progression-free interval of tumor is presumed in the cases. In resource-limited settings, RF ablation can be a safe and available alternative to LITT (Laser Interstitial Thermocoagulative Therapy) that can deliver heat to intracranial tumors.